Opportunities and challenges in stem cell therapy in cardiovascular diseases: Position standing in 2022 - Shabnur Mahmud; Safaet Alam; Nazim Uddin Emon; Umme Habiba Boby; Kamruzzaman; Firoj Ahmed; A.S.M. Monjur-; Afroza Tahamina; Sajib Rudra; Marzina Ajrin (Elsevier, 2022)
This study intends to evaluate the development, importance, pre-clinical and clinical study evaluation of stem cell therapy for the treatment of cardiovascular disease. Cardiovascular disease is one of the main causes of fatality in the whole world. Though there are great progressions in the pharmacological and other interventional treatment options, heart diseases remain a common disorder that causes long-term warnings. Recent accession promotes the symptoms and slows down the adverse effects regarding cardiac remodelling. But they cannot locate the problems of immutable loss of cardiac tissues. In this case, stem cell treatment holds a promising challenge. Stem cells are the cells that are capable of differentiating into many cells according to their needs. So, it is assumed that these cells can distinguish into many cells and if these cells can be individualized into cardiac cells then they can be used to replace the damaged tissues of the heart. There is some abridgment in this therapy, none the less stem cell therapy remains a hopeful destination in the treatment of heart disease.